2013
DOI: 10.1111/opo.12050
|View full text |Cite
|
Sign up to set email alerts
|

The role of luminance and chromatic cues in emmetropisation

Abstract: Citation information: Rucker FJ. The role of luminance and chromatic cues in emmetropisation. Ophthalmic Physiol Opt 2013, 33, 196- Abstract Purpose: At birth most, but not all eyes, are hyperopic. Over the course of the first few years of life the refraction gradually becomes close to zero through a process called emmetropisation. This process is not thought to require accommodation, though a lag of accommodation has been implicated in myopia development, suggesting that the accuracy of accommodation is an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 126 publications
0
70
1
1
Order By: Relevance
“…There have been a significant number of studies examining the effects of temporally and chromatically modulated ambient light on emmetropization (Britton et al, 2013; Crewther and Crewther, 2002; Crewther et al, 2006; Kee et al, 2007; Liu et al, 2014; Liu et al, 2011; Rohrer et al, 1995; Rucker et al, 2015; Rucker, 2013; Rucker and Wallman, 2012; Schwahn and Schaeffel, 1997; Yu et al, 2011), however the results have differed across labs, making them difficult to interpret. Some of this may be due to species differences between chicks, rodents, and primates/near primates, complicated by interactions between the specific wavelengths employed, the number of cones types, and their absorption peaks.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a significant number of studies examining the effects of temporally and chromatically modulated ambient light on emmetropization (Britton et al, 2013; Crewther and Crewther, 2002; Crewther et al, 2006; Kee et al, 2007; Liu et al, 2014; Liu et al, 2011; Rohrer et al, 1995; Rucker et al, 2015; Rucker, 2013; Rucker and Wallman, 2012; Schwahn and Schaeffel, 1997; Yu et al, 2011), however the results have differed across labs, making them difficult to interpret. Some of this may be due to species differences between chicks, rodents, and primates/near primates, complicated by interactions between the specific wavelengths employed, the number of cones types, and their absorption peaks.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in focus of the different wavelengths produce changes in color of the retinal image with defocus (16) , which in turn is reflected in changes in the stimulation of the retinal cones and the retinotectal color and luminance pathways (review: (19) ). A theoretical analysis of the change in the retinal image with defocus has indicated that with myopic defocus, the retina would experience changes in luminance contrast, whereas with hyperopic defocus the retina would also experience changes in color contrast (17) .…”
Section: Introductionmentioning
confidence: 99%
“…There were numerous attempts to identify visual cues that provide the retina with information about the sign of defocus. Longitudinal chromatic aberration was extensively studied (Schaeffel & Howland, 1991;Wildsoet et al, 1993), but it is clear that chromatic cues are at least not obligatory although they may interact with emmetropization (Rucker, 2013;Rucker & Wallman, 2009, 2012. Higher order aberrations could provide a sign of defocus-related cues (Wilson, Decker, & Roorda, 2002) but there is no convincing evidence that they are used during emmetropization (Wallman & Winawer, 2004).…”
Section: Introductionmentioning
confidence: 99%